External control of the Drosophila melanogaster lifespan by combination of 3D oscillating low-frequency electric and magnetic fields. (December 2014) - Makarov, Vladimir I.; Khmelinskii, Igor
Abstract We demonstrate that the lifespan of Drosophila melanogaster population is controllable by a combination of external three-dimensional oscillating low-frequency electric and magnetic fields (3D OLFEMFs). The lifespan was decreased or increased in dependence of the parameters of the external 3D OLFEMFs. We propose that metabolic processes in D. melanogaster's body are either accelerated (in the case of reduced lifespan) or slowed down (in the case of increased lifespan) in function of 3D OLFEMFs that induce vibrational motions on sub-cellular and larger scales.